Hereditarily σ-metacompact function spaces - Junnila, Heikki (Topology Proceedings, 2025)
Let X be a compact space. We consider conditions on X which ensure that the function space C_p(X) is hereditarily σ-metacompact. The conditions involve k-networks with special properties. We prove that C_p(X) is hereditarily σ-metacompact provided that either X has a σ-pointwise-closure-preserving closed k-network or X is supercompact.